Determination of ochratoxin a in wine grapes: comparison of extraction procedures and method validation - Serra, Rita (2004)
A method for determination of ochratoxin A (OTA) in wine grapes is described, using extraction with a hydrogen carbonate and polyethylene glycol (PEG) solution (5% NaHCO3 and 1% PEG 8000), followed by immunoaffinity clean-up and liquid chromatography with fluorescence detection. Validation was made with spiked samples, in levels of 0.05 and 1µg kg−1, with average recovery rates of 76% and relative standard deviations in repeatability and intermediate precision conditions of 8 and 12%, respectively. The limit of detection and limit of quantification in grapes were established at 0.004 and 0.007 µg kg−1, respectively. To evaluate further the accuracy and efficiency of this method, naturally contaminated grapes were also analysed by another method that involves extraction with acidified methanol, at levels ranging from 0.05 to 37 µg kg−1, and the results compared. A good correlation (r = 0.9996) was found, with better performances in terms of precision for the new method. A survey was conducted on wine grapes from 11 Portuguese vineyards, during the harvest of 2002, using the proposed method. OTA was detected in three out of the 11 samples, at levels ranging from 0.035 to 0.061 µg kg−1. The new method meets all the criteria of the European Commission directive 2002/26/CE, that lays down the sampling and the analysis methods for the official control of OTA levels in foodstuffs. It is reliable for low levels of contamination (ng kg−1), and avoids the use of organic solvents in the extraction step. © 2003 Elsevier B.V. All rights reserved.